Histological appearances of oesophagus, antrum and duodenum and their correlation with symptoms in patients with a duodenal ulcer. Issue 1 (January 1985) - Earlam, R J; Amerigo, J; Kakavoulis, T; Pollock, D J
Abstract : Clinical data and histology from the oesophagus, gastric antrum, and duodenum were collected from 36 patients undergoing surgery for duodenal ulcer. Gastritis was present in 94% of the patients (25% of atrophic type), oesophagitis in 72% and duodenitis in 39%. Abnormal biopsies were present from all three sites in 33% of the patients. Only one patient showed three normal biopsies. The low incidence of duodenitis does not support the theory that duodenitis is part of the same spectrum as duodenal ulcer. Heartburn was related to the presence of gastritis (100%) and oesophagitis (76%) but not to duodenitis (52%). No relationship was found between the length of history, severity of pain, and histological abnormalities.